Pengaruh Literasi Keuangan terhadap Pengelolaan Keuangan Mahasiswa: Studi Kasus Mahasiswa Program Studi Pendidikan Ekonomi Universitas Sriwijaya - Venny Fitria; Ikbal Barlian (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine whether Financial Literacy has an effect on the personal financial management of Economic Education students at the Faculty of Teacher Training and Education, Sriwijaya University, Class of 2021 using a quantitative approach through a survey method. Data were collected using questionnaires with purposive sampling and analyzed using Pearson Product Moment correlation test, coefficient of determination, and t-test. The results indicate that financial literacy has a positive and significant effect on students' personal financial management, with a correlation value of 0.8699 and a contribution of 75.76%. The t-test shows that tcalculated t_(calculated )> t_tabel (13.999) is greater than (1.67), confirming the accePTance of the alternative hypothesis. Therefore, students are advised to enhance their financial literacy through various learning sources, while universities are expected to actively contribute to financial education to support students' financial independence.